Kajian Daya Dukung Lahan Perkotaan dalam Rangka Optimalisasi Penataan Ruang Kota Bandung (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
In the context of urban development, it is important to pay attention to the environmental carrying capacity aspect considering that the growth of the urban population with its various activities has led to an increase in the need for space, which is often marked by an increase in the built-up area. If not controlled, this growth can result in an imbalance of urban space requirements with land suitability, indicated by the deficit of urban carrying capacity. This paper aims to describe the condition of land carrying capacity by presenting a series of analyzes related to the urban land suitability and the need for urban space, as well as identification of the status of land carrying capacity in Bandung City. Using a descriptive-quantitative approach accompanied by a spatial analysis at the district level, this study reveals the fact that in 2019 as many as 25 out of 30 urban villages (about 83%) in Bandung City already have a deficit in urban carrying capacity status which indicates that space requirements have exceeded the land suitable for urban areas. The estimates of urban space requirements based on population projections in 2031 produce information that only 2 out of 30 districts have surplus land carrying capacity status. The findings in this study indicate that the Bandung City government needs to immediately reorganize the spatial planning regulation in order to balance the development of the built area with the suitability of urban space.